Agrosilvopasture Pattern In Paslaten Village, Tatapaan District, South Minahasa Regency, North Sulawesi Province - Pontoh, Syalomitha; Ratag, Semuel P.; Pangemanan, Euis F.S.; Ngangi, Charles Reijnaldo (Sam Ratulangi University, 2024)
Agrosilvopasture is part of agroforestry which is a system that can be offered to overcome problems that arise due to land conversion and at the same time to overcome the problem of food availability. This research aims to identify the agro silvopastry pattern implemented in Paslaten Village, Tatapaan District, South Minahasa Regency, North Sulawesi Province. The research was carried out in June-July 2023. In this research, the method used was a survey method using a questionnaire as a guide and field observations. The respondents in this study were 6 people taken based on criteria, namely native residents of Paslaten village and people who own agro silvopasture land. The research results show that the patterns applied by the people of Paslaten Village are random planting patterns and regular planting patterns. For annual woody plants, they are planted in a regular planting pattern and used as land dividers between one land and another. Cloves, nutmeg, and coconut are planted in a regular pattern. Some chickens on agro silvopasture land are kept in cages and some are released into the wild. Pigs on agro silvopasture land are confined; Meanwhile, cattle are tied up and not allowed to find their own food because it will damage the existing plants. Keywords: agro silvopasture, agroforestry, Paslaten Village Abstrak Agrosilvopastura adalah bagian dari agroforestri yang merupakan salah satu sistem yang dapat ditawarkan untuk mengatasi masalah yang timbul akibat adanya alih fungsi lahan dan sekaligus untuk mengatasi masalah ketersediaan pangan. Penelitian ini bertujuan untuk mengidentifikasi pola agrosilvopastura yang diterapkan di Desa Paslaten, Kecamatan Tatapaan, Kabupaten Minahasa Selatan Provinsi Sulawesi Utara. Penelitian dilaksanakan pada bulan Juni-Juli 2023. Dalam penelitian ini metode yang digunakan adalah metode survei menggunakan kuesioner sebagai panduan dan observasi lapangan. Responden dalam penelitian ini berjumlah 6 orang yang diambil berdasarkan kriteria yaitu penduduk asli desa Paslaten dan masyarakat yang memiliki lahan agrosilvopastura. Hasil penelitian menunjukan pola yang diterapkan oleh masyarakat Desa Paslaten yaitu pola tanam acak dan pola tanam teratur. Untuk tanaman tahunan berkayu ditanam dengan pola tanam teratur dan digunakan sebagai pembatas lahan antara lahan yang satu dan lahan lainnya. Untuk cengkeh, pala dan kelapa ditanam dengan pola teratur. Hewan ternak ayam di lahan agrosilvopastura ada yang dipelihara dalam kandang dan ada pula yang dilepasliarkan. Hewan ternak babi di lahan agrosilvopastura dikandangkan, sedangkan ternak sapi diikat dan tidak dibiarkan mencari makan sendiri karena akan merusak tanaman yang ada. Kata kunci: agrosilvopastura, agroforestri, Desa Paslaten